Negotiating Islamic Civilization in Digital Media: A Corpus-Assisted Critical Discourse Analysis of Pesantren in Indonesian Online News - Zaman, Saefu; Fahmi, Royan Nur; Amanat, Tri (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the discursive construction of Islamic boarding schools (pesantren) in Indonesian online media, positioning language as a site of negotiation between historical tradition and contemporary social transformation. As deeply rooted Islamic educational institutions, pesantren function not only as sites of religious knowledge transmission but also as symbols of moral authority contested in the digital public sphere. Their representation in online media is therefore shaped by lexical choices, framing strategies, and patterns of representation reflecting tensions between tradition and modernity.This study aims (1) to map linguistic patterns in media coverage of pesantren and (2) to identify representational strategies used in constructing their public image. It employs a corpus-assisted critical discourse analysis (CACDA) approach, using a corpus of online news articles from mainstream Indonesian media (2025–2026). Data were collected with BootCat and analyzed using AntConc, with findings interpreted through the frameworks of Fairclough and van Dijk.The results reveal two parallel representational tendencies: pesantren are portrayed as custodians of Islamic heritage and moral authority, yet also associated with contemporary social issues through recurring lexical patterns. These linguistic choices, along with syntactic structures and actor representation, function as discursive strategies shaping public perception. The study concludes that online media actively construct meanings of pesantren, negotiating their position between civilizational continuity and contemporary social scrutiny.